Chapter 8 Computational Modelling of the Steps Involved in Photodynamic Therapy - Paterson, Martin J. (InTechOpen, 2012)
Photodynamic therapy (PDT) is a branch of phototherapy that has seen a surge of interest in the last few decades, due to its potential in the treatment of various cancers, infections and heart disease.(Bonnett, 2000) This chapter aims to give an overview of the various photochemical steps involved in PDT as a cancer therapy, and in particular the challenges and insight gained from their theoretical description. After a brief review of PDT in general, in a biological and chemical context, the photochemical steps involved will be discussed, detailing the computational techniques required to model these chemical pathways theoretically. We will detail the methodologies that can currently be applied, as well as their limitations of use at present, and areas requiring further development.